Application of the SCHISM Unstructured Grid Model to Simulate Water Levels and Waves in the Coastal Area of Thanh Hoa - Nghe An During Typhoon Doksuri (2017) - Van Tien, Pham; Quoc Huy, Le; Minh Hoang, Dang; Hong Hanh, Nguyen; Thi Lan, Nguyen; Linh Chi, Dang; Van Khanh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1S, 2025)
This paper presents the initial results of applying the multi-scale unstructured grid model system SCHISM-WWM to simulate water levels and waves for the Thanh Hoa - Nghe An coastal area during the typhoon Doksuri (September 2017). The SCHISM model was chosen for its ability to seamlessly simulate physical processes across multiple spatial scales and the superior computational efficiency of its unstructured grid, making it a potential alternative to traditional structured grid systems like ROMS-SWAN. The comparison of computed results with observational data show that the model can effectively simulate the total water level, with a Nash-Sutcliffe efficiency (NSE) index of 0.94 at Hon Dau and 0.88 at Hon Ngu, and corresponding root mean square errors (RMSE) of 0.17 m and 0.21 m. For waves, the maximum simulated significant wave height (7.15 m) is quite close to the observation from the SIO drifting buoy (7.8 m), with an NSE index of 0.96. These results confirm the potential of SCHISM for detailed forecasting of storm surge and waves, and provide a basis for further research to develop a highly reliable operational forecasting system.